Identification of nurseries areas of juvenile prochilodus lineatus (Valenciennes, 1836) (characiformes: Prochilodontidae) by scale and otolith morphometry and microchemistry - Avigliano, Esteban (2016)
The streaked prochilod Prochilodus lineatus (Valenciennes) is a commercially freshwater species from South America, distributed in the Plata basin. In the present work the morphometry (circularity, rectangularity, form factor, OL/OW and ellipticity indices) and chemistry (Sr:Ca, Ba:Ca, Zn:Ca) of lapilli otolith, and geometric morphometry of scales of streaked prochilod juveniles, in two sites in the Plata basin (Uruguay River and Estrella Wetland), were compared to determine if they are area-specific and to identify possible breeding areas. Otolith Ba:Ca ratios was 0.017±0.003 mmol/mol for Uruguay River while for Estrella Wetland individuals was bellow the detection limits. Zn:Ca ratios tended to be higher for the latter (0.03±0.002 mmol/mol). Significantly high circularity and low rectangularity values were obtained for Estrella Wetland otoliths (p < 0.05), while no significant differences for form factor, OL/OW and ellipticity were observed between sampling sites. Considering all scale geometric morphometry variables, discriminant analysis showed a good percentage of classification of individuals (90.5% for Estrella Wetland and 85.7 % for Uruguay River). These results indicate that the otolith microchemisty and morphometry (circularity and rectangularity indices) and scale morphometry are good markers of habitat and represent a potential tool for identification of streaked prochilod nursery areas.